2019
DOI: 10.1002/jcb.28838
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive circular RNA profiling reveals circ_0002060 as a potential diagnostic biomarkers for osteoporosis

Abstract: Osteoporosis (OP) is a multifactorial and common bone disease worldwide. The clinical diagnosis and treatment of osteoporosis has limitations since changes in bone density occur slightly. Thus, it is critically needed to look for new biomarkers to identify and cure osteoporosis. CircRNAs are important molecular regulators that participate in various biological processes and present tremendous therapeutic potential. The role of circRNAs in osteoporosis remains largely unknown. Here, we explore the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…One study reported that circRUNX2 can sponge miR-203 and promote the expression of osteogenic differentiation-related proteins, such as RUNX2, OCN, OPN, and BSP, consequently preventing osteoporosis [90]. Another study explored the expression of circRNAs using microarray analysis and identified circ_0002060 as a potential diagnostic biomarker and therapeutic target for osteoporosis [91].…”
Section: Circrnas In Other Age-related Diseasesmentioning
confidence: 99%
“…One study reported that circRUNX2 can sponge miR-203 and promote the expression of osteogenic differentiation-related proteins, such as RUNX2, OCN, OPN, and BSP, consequently preventing osteoporosis [90]. Another study explored the expression of circRNAs using microarray analysis and identified circ_0002060 as a potential diagnostic biomarker and therapeutic target for osteoporosis [91].…”
Section: Circrnas In Other Age-related Diseasesmentioning
confidence: 99%
“…OP is a progressive metabolic skeletal condition that increases the fragility fracture risk caused by low bone mass architectural deterioration of bone microstructure because of an imbalance between bone resorption and bone formation 35‐37 . To date, substantial investigations have reported that circRNAs take part in regulating different pathophysiological events, including tumorigenesis, organogenesis and tissue development, and function as biomarkers in various human processes, such as osteoporosis and cancer 38‐40 . In the present study, circRNA expression profiles were evaluated and 4972 circRNAs were significantly expressed in the OP group compared to the non‐OP group.…”
Section: Discussionmentioning
confidence: 84%
“…[35][36][37] To date, sub- cancer. [38][39][40] In the present study, circRNA expression profiles were in transduced hASCs cultured in PM or OM measured by qRT-PCR. G, Western blot analysis detected RUNX2 and OCN protein expression levels on day 7 in transduced hASCs cultured in PM or OM.…”
Section: Discussionmentioning
confidence: 94%
“…Their data identified 203 upregulated and 178 downregulated circRNAs and revealed circ_0001275 was a potential diagnostic biomarker according to qRT-PCR results. Huang et al [ 24 ] performed microarray analysis and PCR validation, and their result showed that circ_0006873 and circ_0002060 were linked to the low BMD state. In our study, rather than investigating by microarray which could identify only thousands of circRNAs, we chose to sequence all circRNAs that were attained in blood samples from patients with newly diagnosed senile OVCF and healthy controls.…”
Section: Discussionmentioning
confidence: 99%